Are clinician ratings useful in evaluating outcomes in Child and Adolescent Mental Health Services (CAMHS)? A study of a continuous series of 1446 cases from an inner city CAMHS. Issue 4 (22nd April 2015) - Fuggle, Peter
Abstract Rationale, aims and objectives Routine outcome evaluation in Child and Adolescent Mental Health Services is an essential part of effective service delivery but it has been hard for services to obtain client‐rated outcomes on more than 50% of cases. Clinician‐rated outcomes are examined whether this would provide a valid and reliable way of contributing to addressing this difficulty. Method This paper will evaluate the pragmatic utility, reliability and validity of a method of measuring clinical outcomes using clinician ratings using an adapted form of the Clinical Global Impressions scale with additional items based on the Every Child Matters framework on a continuous case series of 1446 cases. Results A rating of clinical outcome was obtained on 93% of cases. Approximately 55% of cases were rated as improved and about 30% as showing no change with about 5% reported as being worse. Test‐retest reliability was acceptable (Pearson r = 0.94; P < 0.001) and criterion validity, comparing clinician and parent ratings, showed a significant correlation of 0.42 on severity of problem (Kendall's tau; t = 2.321, P = 0.02) and 0.36 on the degree of improvement (t = 2.637, P = 0.008). Rates of clinical improvement in studies of usual care suggested similar rates to those reported in this study. Conclusions Clinician ratings were obtained for a high proportion of cases and the burden on clinicians was extremely low with negative outcomes similar to known rates of usual care. This high coverage may add value to the evaluation of service outcomes.